O avanço do refúgio climático: uma análise do instituto do refúgio no direito internacional público a partir de condições climáticas degradantes - Carvalho, Mariana Munhoz (2022)
This paper aims to examine the evolution of the concept and treatment of refuge in International Public Law due to the advent of degrading climatic conditions. For this purpose, the environmental protection of human rights and pertinent environmental legislation will be studied, followed by the conceptualization and application of refuge in international law, its protections and other developments. Finally, the causes and application of climate refuge will be observed, considering that poor climatic conditions are able to impact other social rights of the population in a vulnerable state, leading to the need to leave their country and, consequently, to the demand for expansion of the concept of refuge under international law